2017
DOI: 10.3390/ijms18050966
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond-Pulsed DBD Plasma-Generated Reactive Oxygen Species Trigger Immunogenic Cell Death in A549 Lung Carcinoma Cells through Intracellular Oxidative Stress

Abstract: A novel application for non-thermal plasma is the induction of immunogenic cancer cell death for cancer immunotherapy. Cells undergoing immunogenic death emit danger signals which facilitate anti-tumor immune responses. Although pathways leading to immunogenic cell death are not fully understood; oxidative stress is considered to be part of the underlying mechanism. Here; we studied the interaction between dielectric barrier discharge plasma and cancer cells for oxidative stress-mediated immunogenic cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(170 citation statements)
references
References 111 publications
4
162
1
Order By: Relevance
“…A pulsed DBD with microsecond pulses was used for treatment of xenograft model mouse of human glioblastoma cells [23]. Recently, nanosecond-pulsed plasma have been developed as potential tools in cancer treatment [24,25].…”
Section: Direct Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulsed DBD with microsecond pulses was used for treatment of xenograft model mouse of human glioblastoma cells [23]. Recently, nanosecond-pulsed plasma have been developed as potential tools in cancer treatment [24,25].…”
Section: Direct Treatmentsmentioning
confidence: 99%
“…Several recent studies have suggested that non-thermal plasma treatment induces ICD and stimulates macrophages [25,[33][34][35]. Non-thermal plasma treatment was shown to stimulate extracellular ATP secretion and enhance cell death via ICD-mediated macrophage stimulation.…”
Section: Indirect Treatment: Plasma-assisted Cancer Immunotherapymentioning
confidence: 99%
“…Miller et al [160] and Almeida [161] described the detailed principles and possibilities of plasma use in immunotherapy. In particular, the work by Lin et al [162] demonstrated that CAP should induce ICD in vitro in A549 lung cancer and radio-resistant nasopharyngeal carcinoma cell lines. Therein, extracellular ATP secretion was followed by ICD macrophage stimulation.…”
Section: Use Of Cap For Tumour Treatmentmentioning
confidence: 99%
“…Immediately following mechanical disruption, the media was removed, and cells were washed with phosphate buffered saline (PBS). The PBS was then removed, and cultures were treated with NTP using a nanosecond-pulsed dielectric barrier discharge (nspDBD) system ( Figure 1B) [25].…”
Section: Scratch Test and Ntp Treatmentmentioning
confidence: 99%
“…Both electrodes used a nanosecond pulser (FPB-20-05NM, FID GmBH, Burbach, Germany) to generate a high voltage pulse (29 kV, 2 ns rise times, and 20 ns pulse width), and, therefore, the pulse characteristics were the same. While the electrode geometries are different, several studies have demonstrated that the NTP treatment energy is the most crucial effector of biological response with the DBD plasma system [25][26][27]. Therefore, both the voltage and current of the discharge in the system was measured and energy per plasma pulse for both electrodes was calculated as previously described [28]: 0.9 mJ/pulse for the flat DBD electrode and 1.6 mJ/pulse for the pen electrode.…”
Section: Scratch Test and Ntp Treatmentmentioning
confidence: 99%